Comparative Urban Research From Theory To Practice Co-Production For Sustainability - Simon, David; Palmer, Henrietta; Riise, Jan (2020)
"Available Open Access under CC-BY-NC license. Reporting on the innovative, transdisciplinary co-production on sustainable urbanisation undertaken by Mistra Urban Futures, a highly influential research centre based in Sweden (2010-19), this book makes a significant original contribution to evolving theory about comparative urban research and highlights important methodological experiences across multiple diverse contexts in Africa and Europe. Examining specific yet diverse regional and local contexts across Europe, this book uses original research to evaluate differences in scope, approach, orientation, and objectives. It examines the embedding of LLL policies into the regional economy, the labour market, education and training systems and the individual life projects of young people, with a focus on those in situations of near social exclusion. "